Pemberdayaan Masyarakat Desa Talango Sumenep Menuju Desa Tanggap Covid-19 - Choliq, Idham; Syarifurrahman, Islam; Firman; Fitriyani, Vika Ramadhana (Journal of Health Innovation and Community Services, 2022)
Background The pandemic situation has occurred in various regions. It has not been fully controlled properly even though the COVID-19 vaccination continues to be carried out on a massive scale. This occurs because it is not accompanied by public compliance with health protocols. Such conditions exactly describe what happened in Talango village, Sumenep district. Public awareness of the dangers of COVID-19 transmission is still very low, as evidenced by community activities without wearing masks and crowding, not to mention many community groups who think the corona has disappeared. Seeing this, we did empowerment in Sumenep Regency. Objective We carried out several innovative activities such as education about the dangers of COVID-19 transmission. Method Distributing 500 masks is around the Talango port, and spraying disinfectants in several areas, including schools, village halls, port, and Asta Yusuf. Besides, we also made handwashing facilities and distributed hand sanitizer in several areas that were visited by many Talango people. Result Through this activity, it is hoped that the Talango village community will know and become more responsive about the dangers of the coronavirus. Conclution: During this activity, the community seemed enthusiastic about participating in the activity and using the handwashing facilities that we had made. Besides, people's knowledge became better when they were asked about the dangers of COVID-19.